Conductive Co-based metal organic framework nanostructures for excellent potassium- and lithium-ion storage: kinetics and mechanism studies. Issue 17 (10th August 2022) - Mao, Pengcheng; Fan, Huilin; Liu, Chang; Lan, Gongxu; Huang, Wei; Li, Zhipeng; Mahmoud, Hitham; Zheng, Runguo; Wang, Zhiyuan; Sun, Hongyu; Liu, Yanguo
Abstract : Nanostructured Co-CAT metal–organic frameworks show excellent potassium storage performance in terms of high specific capacity, fast charge/discharge and long term storage stability. Abstract : Thanks to the low cost and earth's abundant potassium resources, potassium ion batteries (PIBs) have attracted much interest as alternative energy storage devices. However, there is still a great challenge to develop suitable anode materials for PIBs with high specific capacity, fast charge/discharge and stable ion storage. Nowadays, conductive metal–organic frameworks (c-MOFs) with excellent physicochemical properties are employed for different electrochemical applications, but the study of their potassium storage performance remains unknown, and the detailed potassium storage mechanism needs to be explored. Herein, nanostructured Co3 (HHTP)2 c-MOF (Co-CAT MOF, HHTP: 2, 3, 6, 7, 10, 11-hexahydroxytriphenylene) is synthesized by a liquid-phase method and evaluated as the anode for PIBs. The active sites and open pathways in the conductive Co-CAT MOF promote ion diffusion and electron transfer, exhibiting high reversible specific capacity (332 mA h g −1 at 0.1 A g −1 ), excellent long-cycle stability (230 mA h g −1 at the current density of 1.0 A g −1 after 700 cycles) and outstanding rate performance (165 mA h g −1 at 4.0 A g −1 ), which is superior to the typical PIB anodes. Combined with different ex situ characterization techniques, the potassium storage mechanism based on 8-electron transfer is revealed. Furthermore, Co-CAT MOF exhibits excellent Li-ion storage performance. In the half-cell, the Co-CAT MOF electrode displays a high reversible capacity of 800 mA h g −1 at 200 mA g −1 . In addition, the Co-CAT//LiCoO2 full cell cycles for 100 cycles at 200 mA h g −1 . It is believed that Co-CAT MOF is a promising electrode material for potassium/lithium storage, and the proposed ion storage mechanism can be used to discover other MOF-based electrodes for energy storage.